2007
DOI: 10.1111/j.1542-734x.2007.00511.x
|View full text |Cite
|
Sign up to set email alerts
|

Every Picture Tells a Story: Racial Representation on Sports Illustrated Covers

Abstract: Eric Primm is Assistant Professor of Sociology at Pikeville College in Kentucky. In addition to studying racism in football card collecting, he presently is expanding his research to other sports and to other areas of popular culture such as the motorcycle subculture. Summer DuBois is a graduate student in the sociology department at the University of Colorado. Robert M. Regoli is a Professor of Sociology at University of Colorado. He has authored eleven books and more than one hundred scholarly articles. Prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…During SI's first decade of publication more than 90% of the athletes featured on its covers were white (DuBois and . It is important to note, however, that while this seems like a very high number, the vast majority of athletes in professional baseball (81%), football (86%), and basketball (74%) at this time were white (Primm et al 2007). …”
Section: Discussionmentioning
confidence: 96%
“…During SI's first decade of publication more than 90% of the athletes featured on its covers were white (DuBois and . It is important to note, however, that while this seems like a very high number, the vast majority of athletes in professional baseball (81%), football (86%), and basketball (74%) at this time were white (Primm et al 2007). …”
Section: Discussionmentioning
confidence: 96%
“…If questions and issues arose, the author and coders discussed them, and additional published resources, such as books, magazines, and newspapers, were consulted to resolve any discrepancies. This method is similar to that used by Primm, DuBois, and Regoli (2007) in their examination of race on the covers of Sports Illustrated magazines. The coding categories for gender were 1) male and 2) female.…”
Section: Coding Categoriesmentioning
confidence: 99%
“…For example, Billings and Eastman (2002) found that television coverage of the 2000 Summer Olympics was largely skewed toward White athletes, as this racial group received over 1,200 more mentions than Black athletes throughout the duration of the Games. Similarly, several studies focusing on Sports Illustrated found that White athletes received more coverage than Black athletes (e.g., Condor & Anderson, 1984;Lumpkin & Williams, 1991;Primm, DuBois, &Regoli, 2007). Condor and Anderson (1984) and Lumpkin and Williams (1991) both found that feature stories of White athletes were longer and more in-depth than those articles about athletes of other races.…”
Section: Literature Reviewmentioning
confidence: 96%